Uses and importance of wild fungi: traditional knowledge from the Tshopo province in the Democratic Republic of the Congo - Héritier Milenge Kamalebo; Hippolyte Nshimba Seya Wa Malale; Cephas Masumbuko Ndabaga; Jérôme Degreef; André De Kesel (BMC, 2018)
Abstract Background Wild mushrooms constitute an important non-timber forest product that provides diverse substances and services, especially food and income for local communities from many parts of the world. This study presents original ethnomycological documentation from the dense rainforests of the Democratic Republic of the Congo. Methods Ethnomycological surveys were made within local communities near the biosphere reserve of Yangambi and the Yoko forest reserve. The interviews involved 160 informants from six different ethnic communities (Bakumu, Turumbu, Topoke, Lokele, Ngelema, and Ngando). Specific reported use (RU), the relative importance (RI), and the cultural significance (CS) of wild edible fungi were calculated using quantitative data from enquiries. Results The people from Tshopo use 73 species of wild mushrooms either for food (68 species), as medicine (9 species), in a recreational context (2 species), or related to myths and beliefs (7 species). Women are more involved in harvesting and are the main holders of cultural aspects related to fungi. The results show that knowledge of useful mushrooms differs between ethnic groups. The Ngando people have the highest ethnomycological expertise, which is expressed in their extensive cultural and practical use of fungi. Pleurotus tuber-regium is the most important species (MCSI = 1.9 and p value < 2.2e−16) as it is being used for food, as a medicine, and more. Daldinia eschscholtzii is the most important (MUI = 0.86 and p value < 2.2e−16) for medicinal applications, while Schizophyllum commune, Auricularia cornea, A. delicata, Marasmius buzungolo, and Lentinus squarrosulus are mostly appreciated for food. The latter five species are all wood-decaying saprotrophs. Conclusion Despite the presence of edible ectomycorrhizal taxa in the dense rainforests of Tshopo, local people only seem to have an interest in saprotrophic taxa. Some mushroom pickers deliberately cut down host trees to promote the development of saprotrophic taxa. Inducing forest degradation is considered beneficial as it promotes the development of saprotrophic taxa. The domestication of locally appreciated saprotrophic lignicolous fungi is proposed as a mitigating measure against fellings.